Pengembangan Model Kampung Literasi untuk Meningkatkan Motivasi Pendidikan dan Minat Membaca Masyarakat Desa Kolam Kabupaten Deli Serdang - Sihar Pandapotan; Sondang P. Pakpahan; Syahril Syahril; Antonius Hendrick (Universitas Medan Area, 2020)
The Village Literacy Model Development Program to Increase Motivation in Education and Community Reading Interest was carried out in Kolam Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province. Pond Village has been a major partner since the 2017 program and is supported by other partners such as Posyandu, Karang Taruna, schools in Kolam Village. By building a broad partnership, it is hoped that during the three years the program runs, UPBJJ Open University in Medan will be able to turn the Village Pool into a Literacy Village where the community becomes literate and knowledge literate, thereby increasing the motivation of educating to tertiary institutions. Thus the development and development of human resources (HR) in the Village Pool will increase in the future. This program continues the program achievements in 2017 and 2018 ago. During the implementation of the 2019 National PkM, various activities have been carried out, including providing assistance for renovation of the Pool Village library space, providing mobile assistance for Pool Village library equipment, and providing bookshelves, building information media and literacy campaigns, facilitating book publishing a collection of children's stories, and the launch of the Village Pool as a Village of Literacy.